Superior Electromagnetic Shielding and Mechanical Buffering Achieved by Alternating Conductive and Porous Supramolecular Networks. Issue 7 (22nd January 2022) - Yang, Benqiang; Dai, Keren; Bi, Lei; Zhang, Wenling; Li, Changsheng; Zhang, Jinming; Yu, Da; Wang, Jiong; Zhang, He
Abstract : The development of electromagnetic interference (EMI) shielding materials with excellent EMI shielding effectiveness (SE), and superior mechanical performance is of great importance in daily life and in the military, where they are used for intelligent transportation systems and ammunition. Generally, shielding performances can be realized via reflection loss and absorption loss. However, it is still a challenge to enhance these two kinds of electromagnetic wave loss in the same material at the same time to achieve ideal shielding performance. Herein, a flexible Ag NDs/CNT@PC/Ni‐9 film composed of five conductive layers and four porous layers is prepared by alternating Ag NDs/CNT layers and PC/Ni layers through self‐assembly. The obtained film with a thickness of 890 μm exhibits a remarkable SE performance of 138 dB in the X‐band. Additionally, with a series of continuous volcanic mechanical impacts (>10 000 g), the maximum instantaneous acceleration is decreased by 30.02% due to the buffering of the film, which constitutes a much‐improved energy absorption cushion relative to that of traditional buffering materials, such as foam metal and rubber. A material integrated with strong EMI shielding and high mechanical shock resistance is designed, which provides an effective strategy for the development of functional materials for extreme environments. Abstract : A flexible Ag NDs/CNT@PC/Ni film with high conductivity and sufficient porosity is obtained via self‐assembly. The obtained Ag NDs/CNT@PC/Ni film simultaneously exhibited superior electromagnetic interference shielding effectiveness and mechanical impact buffering properties.